Needs Analysis of Physics Learning Media Development Based on Augmented Reality Technology for High School Students - Hera Anis Kartika; Andik Purwanto; Eko Risdianto (CV Media Inti Teknologi, 2023)
This study aims to examine what educators and learners require in order to create augmented reality-based educational materials for high school students. Descriptive research is one of the study methods used in research and development (RND). The data collection used is by conducting literature studies, observations, interviews and filling out questionnaires. This research instrument consists of observation sheets, interview sheets, and questionnaire sheets. Both quantitative and qualitative data analysis were the methods employed for the data analysis. The findings of the analysis of student needs questionnaires showed that, on average, 69% of the category agreed to the development of augmented reality-based learning media. These findings are based on observations made during teacher interviews, which indicate that the learning media used are still conventional and cause students to struggle with understanding learning materials. Thus, it follows that the utilization of learning materials based on augmented reality is required as a supporting medium in the educational process.